Hang him twice - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Trail west (Series), 2018)
Accidental outlaw Dooley Monahan unexpectedly finds himself first the owner of a silver mine in the lawless boomtown of Leadville, Colorado, and then the town's marshal, which forces him into the crossfire between two rival gangs.